Fatigue of titanium weldments: S-N testing and analysis for data transferability among different joint types. (May 2017) - Xing, Shizhu; Dong, Pingsha
Abstract: Fatigue testing of both TIG and MIG welded titanium components were first carried out using fillet welded cruciform specimens. A mesh-insensitive traction structural stress method is then introduced for establishing data transferability from one joint geometry to another and one base plate thickness to another. In addition, available test data from literature are also analyzed using the traction stress parameter proposed. Major findings are: (a) There exist no noticeable differences in S-N curve behaviors between Ti-CP and Ti-6-4 weldments. (b) The proposed traction stress parameter with a thickness correction term can be used to effectively correlate lab specimen test data in the form of a single S-N curve with a narrow scatter band regardless of joint types and base plate thicknesses, which has been demonstrated for both MIG and TIG welded specimens. (c) By using both the S-N curve and traction stress parameter developed, satisfactory fatigue life estimates for a series of full-scale MIG-welded structural component fatigue tests have been achieved. Highlights: Conducted a systematic fatigue testing on welded titanium (Ti-CP and Ti-6-4) joints. Proposed a traction stress parameter for effective test data interpretation. Proposed S-N curves for fatigue evaluation of TIG and MIG welded titanium components. Found that Ti-CP and Ti-6-4 components follow the same master S-N curve. Validated the effectiveness of the proposed approach using full scale component tests.